Individual and familial factors associated with metabolic control in children with type 1 diabetes. Issue 6 (December 2013) - Demirel, Fatma; Tepe, Derya; Esen, Ihsan; Buber, Nazli; Boztepe, Handan
Abstract Background The aim of this study was to determine the individual and familial factors associated with metabolic control in children with type 1 diabetes (T1DM). Methods The study was performed in 93 children with T1DM between the ages of 3 and 19 years. Children and their families completed questionnaires on sociodemographics and data associated with diabetes. Medical information from the charts was also recorded. Results Older age, longer diabetes duration and higher hospitalization rate for acute complications were positively associated with poor metabolic control. Good school performance, regular hospital visits, young maternal age, high paternal education level and fewer numbers of siblings were found to be negatively associated with poor metabolic control. Conclusions Multiple individual and family‐level factors are associated with metabolic control. These data may aid in identification of diabetic children and adolescents who have a higher risk of poor metabolic control.